Axial oxygen vacancy-regulated microwave absorption in micron-sized tetragonal BaTiO3 particles. Issue 36 (29th August 2018) - Baek, Kyungnae; Lee, Seung-Yong; Doh, Sang-Gil; Kim, Miyoung; Hyun, Jerome K.
Abstract : Microwave absorption of micron-sized BaTiO3 particle composites are enhanced up to −26 dB by effective control over ferroelectric domain wall motion mediated by axial oxygen vacancies. Abstract : Ferroelectric micro and nanostructures have recently emerged as potential candidates for managing microwave absorption in the GHz range. While various loss mechanisms accounting for the high absorption have been proposed, the contribution of energetically stable axial oxygen vacancies in tetragonal lattices has not been definitively addressed for such structures. In this study, we explore the modulation of microwave absorption in micron-sized BaTiO3 particles through the incorporation of such oxygen vacancies while controlling for differences in particle size, grain size and crystalline phase. Raman, electron paramagnetic resonance (EPR) and electron energy loss spectroscopy (EELS) analysis were used to identify axial oxygen vacancy complexes in BaTiO3 particles of varying degrees of oxygen-deficiency. Measurements of the complex permittivity and permeability for BaTiO3 particles/polyurethane composites across the range from 1 to 18 GHz showed behavior dominated by dielectric relaxation, and a 35% enhancement in dielectric loss for a ∼15 fold increase in oxygen vacancy concentration, attributed to slowing of domain wall movement. An improvement in maximum reflection loss values from −16.9 dB to −43.2 dB was also demonstrated through the incorporation of oxygen vacancies in the particles. Such results suggest that control over the oxygen vacancy concentration can be used as an effective means for freely tuning the microwave absorption in the technologically relevant S, C, and X bands.